Extracellular matrix hydrogels from decellularized tissues: structure and function - Saldin, Lindsey T.; Cramer, Madeline C; Velankar, Sachin S; White, Lisa J.; Badylak, Stephen F. (Elsevier, 2017)
Extracellular matrix (ECM) bioscaffolds prepared from decellularized tissues have been used to facilitate constructive and functional tissue remodeling in a variety of clinical applications. The discovery that these ECM materials could be solubilized and subsequently manipulated to form hydrogels expanded their potential in vitro and in vivo utility; i.e. as culture substrates comparable to collagen or Matrigel, and as injectable materials that fill irregularly-shaped defects. The mechanisms by which ECM hydrogels direct cell behavior and influence remodeling outcomes are only partially understood, but likely include structural and biological signals retained from the native source tissue. The present review describes the utility, formation, and physical and biological characterization of ECM hydrogels. Two examples of clinical application are presented to demonstrate in vivo utility of ECM hydrogels in different organ systems. Finally, new research directions and clinical translation of ECM hydrogels are discussed